The cognitive component of elite high jumpers` preperformance routines - Gretton, T.; Blom, L.; Hankemeier, D.; Judge, L. (The Sport Psychologist, 2020)
Preperformance routines are microlevel performance processes utilized by athletes to facilitate the attainment of an optimal state and enhance the chance for successful performance. Despite continued examination of these routines, only a small proportion of research has been directed toward the cognitive component of these routines. This study explored the cognitive component of elite high jumpers` preperformance routines, and specifically the consistency of the cognitive content (i.e., psychological skills and strategies). Data were acquired over an 8-week high-jump season and subjected to inductive thematic analysis. Results revealed the consistent implementation of the cognitive content (e.g., visualization) but an inconsistent design of this content (i.e., the content of the visualization). Furthermore, results underline the critical role of high-jump coaches and an athlete`s need to be adaptable and competent in utilizing various types of preperformance routine. This study offers valuable insight into the complexities and inconsistencies of the cognitive component of high jumpers` preperformance routines.